The title(s) of Menander’s Sikyonioi - Favi, F (Brill Academic Publishers, 2019)
The title of Menander’s Sikyonioi has long posed major critical challenges.1 While the earliest sources, the colophon of the Sorbonne papyrus (third century BCE) and a wall painting from Ephesus (second century CE), attest to the masculine plural title Σικυώνιοι,2 later indirect sources quoting fragments from the play transmit the masculine singular title Σικυώνιος;3 two indirect sources also testify to the existence of a feminine singular title Σικυωνία.4 It is now quite widely agreed upon that Σικυώνιοι is the correct title for the play, not least